Modeling Islamic Economics and Finance Research: A Bibliometric Analysis - Rusydiana, Aam; Sanrego, Yulizar; Rahayu, Solihah (Universitas Muhammadiyah Yogyakarta, 2021)
This study aims to determine the development map of mathematic model in islamic economics and finance research that is indexed by Scopus and other reputable journal with the keyword